SISTEM PENGAMBILAN KEPUTUSAN UNTUK EMPLOYEE AWARD MENGGUNAKAN ANALYTICAL NETWORK PROCESS - Elfahmi, Azzati Sahirah; Rachmadewi, Ira Promasanti; Qurtubi; Mujafar, Iqbal Hilal (Metode : Jurnal Teknik Industri, 2024)
PT FGH is a state-owned company that annually holds an Employee Award to appreciate and motivate the company's workers or employees. Currently, the company is still carrying out the process of selecting the best employees through analysis and manual calculations in the form of average values of the criteria set by the company, which causes this process to take a long time. There is no weighting of criteria and methods or application of a decision support system in selecting the best employees. This research aims to conduct a decision-making system by applying a ranking method that can simplify calculations in determining the best employees by considering factors and relationships between criteria. The method used is the Analytic Network Process method with the help of Super Decision Software. The results of this research from five alternative employees based on four criteria, namely personal aspect, community aspect, organizational aspect, and management aspect, obtained the best employee, namely employee 1, with an ideal weight value of 1.